The Influence of Community on EFL Students’ Motivation in Learning English - Novita Diana; Jamaliah Jamaliah; Salsabila Salsabila; Diana Devi (Ma'soem University, 2026)
This study investigated the influence of community on EFL students’ motivation in learning English. Students’ motivation was regarded as an essential factor in language learning success, yet it was strongly affected by external environments. This study describes how these three environments, such as family, school, and community shaped students’ motivation, to identify their specific impacts, and to determine which factor had the most dominant influence. The research employed a qualitative case study design. Participants were thirty eleventh-grade students from Sukma Bangsa Pidie Senior High School. The data were analyzed descriptively using thematic analysis to identify patterns of influence that supported students’ motivation. The findings revealed that family, school, and community each contributed differently to students’ motivation. Family support mainly provided emotional encouragement, such as praise, parental guidance, and discussions about the importance of English. The school created structured academic reinforcement through engaging teaching methods, teachers’ encouragement, and peer collaboration. Meanwhile, community factors including peers outside school, social recognition, and societal expectations shaped students’ awareness of English as a tool for success. Among these three, the school environment appeared as the most dominant factor in sustaining students’ motivation. In conclusion, this study showed that EFL students’ motivation was the result of interconnected support from family, school, and community. It was suggested that families provide continuous encouragement, schools apply innovative and student-centered strategies, and communities offer authentic opportunities for practicing English.